Learning objects: resources for instruction. - Brickell J; Kanuth M; Freeman V; Latshaw S; Larson C (Clinical Laboratory Science)
OBJECTIVE: Upon completion of this article, the reader will be able to describe learning objects (LOs) and discuss their use in clinical laboratory sciences instruction. DESIGN: Through a questionnaire, educators evaluated clinical laboratory sciences-related LOs for accessibility, usability and instructional qualities. SETTING: LOs were presented on a password-accessed website. Evaluations were completed on the website. PARTICIPANTS: Nine educators participated in the evaluation. INTERVENTIONS: The LOs were made available to participants for use in their own instructional material. MAIN OUTCOME MEASURE(S): The evaluation measured educators' interest in and perceived usefulness of LOs in clinical laboratory sciences curriculum. RESULTS: On a scale of one to five with one equal to poor and five equal to excellent, participants rated LOs as accessible (4.68) and usable (4.61). Ninety-eight percent stated that they would use LOs in their curriculum. Fifty-seven percent stated that they could attribute improved learning performance on student exposure to LOs. CONCLUSION: LOs are useful, relevant, and time-saving resources to clinical laboratory sciences instruction.